Potent Th2 Cytokine Bias of Natural Killer T Cell by CD1d Glycolipid Ligands: Anchoring Effect of Polar Groups in the Lipid Component. Issue 31 (29th June 2018) - Inuki, Shinsuke; Kashiwabara, Emi; Hirata, Natsumi; Kishi, Junichiro; Nabika, Etsuko; Fujimoto, Yukari
Abstract: Th2‐biasing CD1d ligands are attractive potential candidates for adjuvants and therapeutic drugs. However, the number of potent ligands is limited, and their biasing mechanism remain unclear. Herein, a series of novel Th2‐biasing CD1d glycolipid ligands, based on modification of their lipid part, have been identified. These have shown high binding affinities and efficient Th2 cytokine production. Importantly, the truncated acyl chain containing variants still retain their binding affinities and agonistic activities, which can be associated with an "anchoring effect, " that is, formation of a buried hydrogen bond between a polar group on the acyl chain and the CD1d lipid‐binding pocket. The analysis indicated that the appearance rates of ligand–CD1d complexes on the cell surface were involved in Th2‐biasing responses. The designed ligands, having the anchor in the shorter lipid part, are one of the most potent Th2‐biasing ligands among the known ligands. Abstract : Anchors aweigh ! Th2‐biasing CD1d ligands have attracted much attention as potential candidates for vaccine adjuvants and therapeutic drugs. Described here is a series of potent Th2‐biasing CD1d ligands based on an "anchoring effect" of the polar group within the lipid component. These ligands induce high levels of Th2 cytokine production. The length of the polar‐group‐containing acyl chain was significantly correlated with the Th2‐biasing response.